The Role of Arterial Stiffness in the Estimation of Cardiovascular Risk in Liver Transplant Recipients. Issue 1 (23rd December 2021) - Sastre, Lydia; García, Raquel; Gándara, Julián-Gonzalo; Fernández-Llama, Patricia; Amor, Antonio J.; Sierra, Cristina; Escudé, Laia; Ruiz, Pablo; Colmenero, Jordi; Ortega, Emilio; Navasa, Miquel; Crespo, Gonzalo
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Long-term cardiovascular (CV) events are a frequent cause of death and disability after liver transplant (LT). Although a more in-depth, risk-adapted control of CV risk factors may result in improved post-LT CV outcomes, an accurate stratification of the CV risk of LT recipients to better implement preventive strategies is lacking. Aortic pulse wave velocity (aPWV) is a surrogate of arterial stiffness that has been suggested as a biomarker of CV risk; it has never been evaluated in adult LT recipients. Methods: In a single-center prospective study, we included 122 LT recipients at 12 (n = 39), 60 (n = 45), or 120 (n = 38) mo after LT. aPWV estimation by oscillometry, clinical assessment of CV risk factors, and CV risk estimation by standard clinical scores (systematic coronary risk evaluation and pooled cohort equation) were performed. The incidence of CV events during prospective follow-up was registered. Results: aPWV was independently associated with age and the grade of control of blood pressure. After a median follow-up of 35 mo, 15 patients (12%) presented a CV event. Higher aPWV, diabetes, past or present smoking habit, previous CV events, lower eGFR, being in systematic coronary risk evaluation or pooled cohort equation high-risk groups, and higher levels of total cholesterol, LDL-cholesterol, creatinine, and triglycerides were associated with the incidence of CV events at univariate analysis; aPWV, past or present smoking habit, and triglycerides were independent predictors of CV events. Conclusions: According to our results, aPWV mirrors CV risk in LT recipients and thus may be a useful CV risk biomarker in this population. Considering these preliminary results, its accuracy in stratifying risk requires confirmation in further studies. Abstract :